A study on implementing color-batching with selectivity banks in automotive paint shops. (July 2017) - Sun, Hui; Han, Jianming
Highlights: Two batching strategies, conventional and integrated resequencing, are considered. Four physical and virtual resequencing approaches to color batching are presented. Integrated resequencing generally performs better than conventional resequencing. Abstract: The color-batching problem is frequently raised in automotive paint shops. This paper focuses on the implementation issues in obtaining color-oriented batches of cars with selectivity banks prior to painting. Two batching strategies, conventional physical resequencing and integrated physical & virtual resequencing, are considered. A rule-based fill approach and a heuristic-based release approach are presented, which can be jointly utilized on a rolling horizon basis when the strategy of conventional resequencing is applied. Moreover, two virtual resequencing techniques are introduced, both of which can be individually integrated into physical resequencing while integrated resequencing is used. Computational experiments are carried out to evaluate the performance of the proposed strategies and approaches. It is shown that integrated resequencing can generally obtain noticeably better batching results than conventional resequencing. Additionally, the impact of several factors on color-batching, including bank configuration, WIP, and size of look-ahead area, are discussed.